Copy Number Variations in Short Tandem Repeats Modulate Growth Traits in Penaeid Shrimp Through Neighboring Gene Regulation - Hao Zhou; Guangfeng Qiang; Yan Xia; Jian Tan; Qiang Fu; Kun Luo; Xianhong Meng; Baolong Chen; Meijia Chen; Juan Sui; Ping Dai; Xupeng Li; et al. (Animals)
Penaeid shrimp, with its genomes enriched in short tandem repeats (STRs), presents an ideal model for studying the distribution and biological functions of STRs. In this study, we systematically identified and compared STRs across multiple species, confirming a significantly higher prevalence of STRs (26–32%) in penaeid shrimp, which is markedly higher than that observed in other species, such as mammals (1.3–2.1%) and plants (0.21–0.73%). Further analysis utilizing a cohort of 326 Pacific white shrimp revealed a total of 672,507 high-quality STRs evenly distributed across the genome, with a notably lower frequency of SNPs within these STR regions. Focusing on growth traits as a case study, we conducted a genome-wide association study (GWAS) and correlation analyses to identify the regulatory relationship of STRs on complex traits. We discovered 84 STRs that showed a significant association with body weight. Interestingly, eleven of these STRs, with 81% being composed of an A/T base, showed a significant linear correlation with body weight, revealing the key role of A/T-related STRs in shrimp weight regulation. For instance, a significant association and a negative correlation were found between the copy number of the STR [(A)n] at NW_020872788.1:580574 and body weight. The cytokinesis protein 7-like (LOC113800912) gene, which contains this STR in its splice region, exhibits differential expression associated with body weight variation. These findings introduce a model for STR copy number regulation in non-human species, illuminating the influence of STRs on growth traits. It offers a valuable framework for investigating complex traits and the biological functions of STRs in agricultural animals.